Islamic Communication Model in Therapeutic Communication Practices at Adam Malik Hospital - Syafruddin Ritonga; Zamri; Selamat Riadi; Zakaria Siregar (Budapest International Research and Critics University, 2020)
Studies on Therapeutic Communication, especially its relationship to Islamic communication, are still rarely found in the field. This study aims to see how the practice of Islamic communication can be done well by doctors and nurses. This research uses a qualitative approach. The values of Islamic communication in Therapeutic communication can be seen from the way communication is carried out by doctors and nurses with their patients through ethics and good language. The implementation model of Islamic communication in therapeutic communication produces a marker communication model, that is, communication carried out on the basis of the awareness of the medical team. This communication model is not formally implemented, but in substance has similarities with the value of Islamic communication.